«Հալէպ» հայրենակցական բարեսիրական հասարակական կազմակերպության աջակցությունը Սիրիայից հայրենադարձներին (2013–2018 թթ.) - Ավագյան, Քնարիկ (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Начиная с марта 2011 г., с эскалацией военных действий исламистских террористов в Сирии,число сирийских армян, желающих репатриироваться в Армению, увеличилось. В общей сложности, с начала войны до 2018 г. на Родину прибыло 22 000 сирийских армян․ Beginning from March, 2011, along with the escalation of hostilities by Islamist terrorists in Syria, the number of Syrian-Armenians wishing to repatriate to Armenia increased. Totally, from the beginning of the war till 2018, 22,000 Syrian Armenians arrived to Motherland.
Keywords: Armenian Diaspora